Simple Method for Converting Conventional Face-bow to Postural Face-bow for Recording the Relationship of Maxilla Relative to the Temporomandibular Joint. - Ali Gooya; Houman Zarakani; Yeganeh Memari (Tehran University of Medical Sciences, 2015)
A fundamental assumption in prosthetic dentistry is that the axis-orbital plane will usually be parallel to the horizontal reference plane. Most articulator systems have incorporated this concept into their designs and use orbitale as the anterior reference point for transferring the vertical position of the maxilla to the articulator. Clinical observations of Cantonese patients suggest that in some individuals the Frankfort plane may not be horizontal, thus the orientation of the casts in the articulator is incorrect with respect to the horizontal plane. The purpose of this study was to introduce a simple method for converting the conventional face-bow to postural face-bow to reproduce the orientation of the occlusal plane relative to the true horizontal plane with the patient in Natural Head Posture (NHP).